Дослідження в Овруцькому та Лугинському р-нах Житомирської обл. у 2009 р. - Павленко, С.В.; Томашевський, А.П.; Борисов, А.В.; Переверзєв, С.В. (Археологічні дослідження в Україні, 2010)
In 2009, the archaeological prospecting on the territory of Obruch and Luhyny Regions in Zhytomyr Oblast was ongoing. The territory of about 480 km2 was examined, 22 new sites dated from the Mesolithic and Copper Ages to the Late Mediaeval times were discovered, and the condition of some known monuments was checked.